Impact of ethyl alcohol nasal treatment on hospital-onset Staphylococcus aureus bacteremia at a tertiary health system - Donna Nucci; Jennifer H. Sather; Michael Aniskiewicz; Scott C. Roberts (Infection Control & Hospital Epidemiology, 2026)
Abstract Introduction: Staphylococcus aureus is a common pathogen that can cause nosocomial infection. Ethyl alcohol has emerged as a potential alternative to mupirocin and povidone-iodine for nasal decolonization; however, data on real-world application are limited. Methods: A quasi-experiment study was performed. Twice daily 62% ethyl alcohol nasal swabs were offered to inpatients at risk for MRSA acquisition. Compliance was monitored and reasons for non-adherence were evaluated. Rates of hospital-onset S. aureus bacteremia were compared pre and postintervention. Results: A total of 274,999 doses of ethyl alcohol were administered to 12,179 high-risk inpatients with a compliance rate of 82.7%. Reasons for non-compliance centered on product characteristics, patient comorbidities, and perceived lack of benefit from patients and healthcare personnel. There were fewer overall hospital-onset S. aureus bacteremia events (1.97 events/10,000 patients days predecolonization compared to 1.49 events/10,000 patient days with decolonization, P = .013). This difference was primarily driven by reduced MRSA bacteremia events (0.61 events/10,000 patient days predecolonization versus 0.36 with decolonization, P = .009) rather than MSSA bacteremia events (1.31 events/10,000 patient days predecolonization versus 1.13 events/10,000 patient days with decolonization, P = .232). On a per-patient basis during the intervention period, there were fewer MRSA bacteremia events in patients receiving decolonization (6.57 events per 10,000 patients) compared to high-risk, but eligible, patients who did not receive decolonization (19.62 episodes per 10,000 patients, P = .044). Conclusion: Twice daily ethyl alcohol nasal treatment may be a viable alternative to existing S. aureus nasal decolonization options.